A COMPARATIVE STUDY OF FETOMATERNAL OUTCOME IN WOMEN WITH OLIGOHYDRAMNIOS INDUCED WITH MISOPROSTOL - BHATI, ANJLINA; NAGAR, JYOTI; MAYANKJAIN; RAHAR, MONIKA; SURENDRASINGH; RAVIKRISHAN, AISHWARYA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of this study were to compare the effect of misoprostol on fetomaternal outcome among women with oligohydramnios and normal amniotic fluid. Methods: An intervention study was carried out at Obstetrics and Gynecology Department of Jhalawar Medical College during September 2021–February 2022. Based on inclusion and exclusion criteria, 42 women with oligohydramnios at term gestation (Group I) and 42 matched control (Group II) were enrolled in the study. All women were undergone for induction of labor using 50 microgram misoprostol. Data were entered and analyzed using SPSS 23.0 software. Results: Mean age of Group I was 25.9±4.3 and Group II was 26.4±5.8 years. Nearly, equal dose of misoprostol was required to induce labor in both groups (p=0.28). Induction to delivery interval was significantly different (p=0.0001) in both group. Vaginal or assisted vaginal delivery was occur in 26 (61.90%) and 23 (54.76%) in Group I and Group II. Meconium staining was found significantly higher (p=0.033) among Group I (13, 30.95%) than Group II (05, 11.90%). APGAR score <7 at 1 min was found in 11 (26.19%) in Group I and 04 (9.52%) in Group II p=0.046). Conclusion: Labor induction at term with misoprostol in both groups did not show significant difference as far as maternal outcome was concerned, although it does affect neonatal parameters in terms of meconium staining and APGAR score.